2006
DOI: 10.1002/jhm.85
|View full text |Cite
|
Sign up to set email alerts
|

Core competencies in hospital medicine: Development and methodology

Abstract: These competencies should be a common reference and foundation for the creation of hospital medicine curricula and serve to standardize and improve inpatient training practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 10 publications
0
45
0
Order By: Relevance
“…This study also shows that SBML‐trained residents displayed higher self‐confidence and performed significantly more bedside procedures than traditionally trained residents and more experienced hospitalist physicians. Although the Society of Hospital Medicine considers thoracentesis skills a core competency for hospitalist physicians, we speculate that some hospitalist physicians had not performed a thoracentesis in years. A recent national survey showed that only 44% of hospitalist physicians performed at least 1 thoracentesis within the past year .…”
Section: Discussionmentioning
confidence: 92%
“…This study also shows that SBML‐trained residents displayed higher self‐confidence and performed significantly more bedside procedures than traditionally trained residents and more experienced hospitalist physicians. Although the Society of Hospital Medicine considers thoracentesis skills a core competency for hospitalist physicians, we speculate that some hospitalist physicians had not performed a thoracentesis in years. A recent national survey showed that only 44% of hospitalist physicians performed at least 1 thoracentesis within the past year .…”
Section: Discussionmentioning
confidence: 92%
“…The Society of Hospital Medicine (SHM) has established core competencies for hospitalists who manage patients with ACS, defining the scope of interactions between the hospitalist, patient, and other clinicians such as specialists and primary care providers (PCP) 4, 5. Several competencies focus on ACS and transitions in care, requiring the hospitalist to demonstrate the skills and attitudes outlined in Table 1.…”
Section: Core Hospitalist Competencies For Acs Relative To Transitionmentioning
confidence: 99%
“…The complexities associated with practicing in this field were clarified in 2006 when the Society of Hospital Medicine identified 51 core competencies in hospital medicine. 3,6 Some hospitalist programs are willing to provide their PAs with onthe-job training, but many programs do not have the educational expertise or the resources to make this happen. Structured and focused postgraduate training in hospital medicine seems like a reasonable solution to prepare newly graduating PAs that are interested in pursuing hospitalist careers, but such opportunities are very limited.…”
mentioning
confidence: 99%